Clinical Profile, Laboratory Findings And Quality of Life in 100 Patients With Chikungunya Virus Infection - 2025 Outbreak In Bangladesh (Bangladesh Journal of Medicine, 2025)
Background: After a period of absence, a resurgence of chikungunya has been seen in Bangladesh. Therefore, this study aimed at to detect the clinical spectrum, laboratory parameters, and quality of life (QoL) of chikungunya patients during the 2025 outbreak. Methods: This observational study was carried out at Popular Medical College Hospital, Bangladesh, over a period of 3 months, including 100 adult chikungunya patients. QoL was assessed using the EQ-5D-3L (European Quality of Life 5 Dimensions 3 Level Version) tool. Results: The mean (SD) age was 50.6 (18) years with female (61%) predominance. Common manifestations were joint pain (96%), fever (86%), myalgia (57%), and rash (53%). Frequently involved joints were ankle (71%), proximal interphalangeal (60%), metacarpophalangeal (58%), and distal interphalangeal (54%) joints. Chikungunya was confirmed by polymerase chain reaction (59%) and anti-chikungunya IgM (41%). Laboratory findings showed leukopenia (19%) and thrombocytopenia (24%). QoL assessment revealed problems with mobility (62%), usual activities (71%), self-care (51%), pain/discomfort (64%), and anxiety/depression (27%). The mean (SD) and median (IQR) for EQ-VAS (EuroQol Visual Analogue Scale) score were 43.9 (22.2) and 40 (30-63), respectively. Conclusion: Common clinical presentations were fever and joint pain with a high preponderance to ankle and hand joints. Few patients had leukopenia and thrombocytopenia. Most patients suffered from poor QoL.Bangladesh J Medicine 2025; 36(3): 83-90